2020
DOI: 10.1186/s12909-020-02132-2
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer knowledge and perceived barriers to help seeking among pre-clinical and clinical female medical students of King Edward Medical University, Lahore: a cross-sectional study

Abstract: Background Breast cancer is the most common form of cancer in women and second most common cancer after lung cancer. The prognosis of breast cancer depends on early detection and intervention which in turn relies upon awareness. Health workers in all communities are responsible for educating the population at risk. This study evaluates the knowledge regarding breast cancer, personal judgment of confidence, perceived barriers to help seeking and breast self-examination practices among Pakistani fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 24 publications
3
10
2
1
Order By: Relevance
“…Symptoms related to changes in breast appearance were the most difficult to identify by both groups. Similar results were observed by Qasim et al [ 31 ]. This may be due to information campaigns focusing on the presence of lumps and downplaying the importance of other symptoms that are nonspecific to breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Symptoms related to changes in breast appearance were the most difficult to identify by both groups. Similar results were observed by Qasim et al [ 31 ]. This may be due to information campaigns focusing on the presence of lumps and downplaying the importance of other symptoms that are nonspecific to breast cancer.…”
Section: Discussionsupporting
confidence: 92%
“…Further-more, studies must be conducted that analyze the curriculum and clinical training of medical students in Pakistan to identify what learning experiences have greatest impact. 10 The study conducted in Ardebil revealed that both age and marital status had an impact on individuals' knowledge concerning breast self-examination (BSE). 17 Awareness about breast self-examination should be emphasized.Offering elective courses covering women's health can be bene cial for female.…”
Section: Education Status Discussionmentioning
confidence: 99%
“…Contudo, esse valor acima de 90% não foi observado em pesquisa paquistanesa, em que apenas 62,4% acertaram a resposta. Valor que pode ser considerado baixo, visto que essa pesquisa foi realizada apenas com mulheres universitárias do 2º e 3º ano do curso de medicina 17 .…”
Section: Discussionunclassified